The Perception on the Importance and Actual Practice of Top Management Commitment and Leadership in Palm Oil Mill Benchmarking Implementation - Mahmud, atimah; Md Deros, Baba; Abdul Wahab, Dzuraidah; Nizam Ab Rahman, Mohd (International Journal of Engineering and Technology, 2018)
The palm oil industry is the backbone of Malaysian commodities market that contributed to the nation economic stability. In order to sustain and stay competitive, this industry needs to continuously improve its productivity and process efficiency. Benchmarking techniques can be used to identify and investigate palm oil industry best practices adopted by palm oil planters and millers. Past studies showed that the success of benchmarking initiative is very much dependent on top management’s commitment and leadership. This paper aims to discuss managers’ perception on the importance and actual practice of eight attributes of top management’s commitment and leadership in palm oil mills benchmarking implementation and the relationship of attribute’s actual practice with company age. A survey questionnaire was sent to 350palm oil mill’s middle managers in Malaysia. The survey response rate was 51%. Analysis of the survey results shows significant differences between respondents’ perception on the importance and actual practice of the eight attributes of top management’s commitment and leadership. In other words, they have high perception of importance for the eight attributes; however, in reality the practice of attributes is still low.The actual practice of each attributes decreased as the company age increased. In conclusion, to ensure benchmarking implementation success, top management need to practice these attributes systematically.